IMPLIKATUR PERCAKAPAN SEBAGAI REPRESENTASI MAKNA TERSIRAT DALAM NOVEL LARA ATI KARYA BAYU SKAK, TINJAUAN PRAGMATIK TEORI GRICE - monika (Jurnal Lazuardi, 2026)
This study aims to describe conversational implicature as a representation of implied meaning in the novel Lara Ati by Bayu Skak through a pragmatic perspective based on Grice’s theory. The research employed a descriptive qualitative approach with data sources derived from dialogues between characters in the novel. Data were collected through documentation, intensive reading, and systematic note-taking of utterances containing implicatures. Data analysis was conducted through data reduction, coding, classification, and contextual interpretation using Grice’s cooperative principle and conversational maxims. The findings reveal three main types of implicature: conventional implicature, generalized conversational implicature, and particularized conversational implicature. Conventional implicatures appear through lexical and structural elements with stable semantic meanings, while generalized conversational implicatures emerge through common pragmatic inference that does not require highly specific contexts. Particularized conversational implicatures are the most dominant and complex forms, as they rely heavily on situational context, interpersonal relationships, and indirect communication patterns rooted in cultural norms. The study also shows that violations of relevance and quantity maxims function as strategic pragmatic devices used by characters to convey indirect refusals, satire, humor, nostalgia, and implicit emotional expressions. These findings indicate that implicature in the novel functions not only as a linguistic phenomenon but also as a narrative strategy that reflects social values, cultural communication patterns, and character development. This research contributes to the development of Indonesian literary pragmatics and broadens the understanding of implied meaning in contemporary fictional discourse.